Temperature Dependent FT IR Spectroscopic Study of The Interaction of alfa Tocopherol and alfa Tocopheryl Acetate with Phospholipid bilayers - Davies, J. Eric D.; AKYÜZ, SEVİM (Elsevier, 1997)
FTIR spectroscopy has been employed in order to investigate α-tocopherol (α-T) and α-tocopheryl acetate (α-TA) induced effects on the molecular organization of dimyristoyl-l-α-phosphatidylcholine (DMPC) bilayers, at various temperatures and concentrations. It was concluded that α-T interacts much more strongly than α-TA, indicating that α-T has a more polar location in the membrane than α-TA. The observed changes in the carbonyl and phosphate group vibrational modes of DMPC on addition of α-T or α-TA are discussed
Keywords: α-Tocopherol; α-Tocopheryl acetate; Dimyristoyl-l-α-phosphatidylcholine; DMPC; Bilayers; FTIR